VD_FINDINFO ML / 2011 / 323 vom 30. Dezember 2011 - VD Tribunal cantonal (2011)
ACTE DE RECOURS, CONDITION DE RECEVABILITÉ, SIGNATURE, INTÉRÊT DIGNE DE PROTECTION | 130 al. 1 CPC (CH), 132 al. 1 CPC (CH), 59 al. 1 CPC (CH), 59 al. 2 let. a CPC (CH)